Efficacy of encapsulated fecal microbiota transplantation and FMT via rectal enema for irritable bowel syndrome: a double-blind, randomized, placebo-controlled trial (CAP-ENEMA FMT Trial) - Aumpan, Natsuda; Chonprasertsuk, Soonthorn; Pornthisarn, Bubpha; Siramolpiwat, Sith; Bhanthumkomol, Patommatat; Issariyakulkarn, Navapan; Gamnarai, Pornpen; Bongkotvirawan, Phubordee; Wongcha-um, Arti; Mahachai, Varocha; Vilaichone, Ratha-korn (Frontiers in Medicine, 2025)
IntroductionIrritable bowel syndrome (IBS) is a functional bowel disorder. Gut dysbiosis involves in pathogenesis of IBS. Limited studies compared efficacy of fecal microbiota transplantation (FMT) via different routes of administration. This study aimed to compare efficacy of encapsulated FMT, FMT via rectal enema, and placebo in IBS patients.MethodsIn this double-blind, randomized, placebo-controlled study, we enrolled patients aged 18–70 years with IBS defined by Rome IV criteria at Thammasat university, Thailand. Patients were randomized into three groups: (1) encapsulated FMT (six capsules twice daily for two consecutive days, total 50 g of stool), (2) FMT via rectal enema (50 g of stool in 200 mL of isotonic saline), or (3) placebo. Primary endpoint was clinical response defined by ≥50-point decrease in IBS-symptom severity score (IBS-SSS) at 4 weeks. Secondary outcomes were quality of life and changes of fecal microbiota composition after treatment. The study was registered with ClinicalTrials.gov, number NCT06201182.ResultsFrom August 20, 2020, to February 15, 2024, 45 patients were randomized to receive encapsulated FMT (n = 15), FMT via rectal enema (n = 15), or placebo (n = 15). There was no difference in patient characteristics and baseline IBS-SSS between groups. Encapsulated FMT provided significantly improved IBS-SSS (166.7 ± 73.7 vs. 269.3 ± 69.5, p = 0.001), clinical response (86.7 vs. 26.7%, p = 0.001), and quality of life (31.7 ± 4.8 vs. 25.1 ± 5.2, p < 0.001) at 4 weeks compared with placebo. FMT via rectal enema demonstrated better IBS-SSS (168.7 ± 101.9 vs. 269.3 ± 69.5, p = 0.004), clinical response (73.3 vs. 26.7%, p = 0.011), and quality of life (30.2 ± 5.0 vs. 21.0 ± 7.4, p < 0.001) than placebo. Clinical response and quality of life between encapsulated FMT and FMT via rectal enema were not different. No serious adverse event was observed. Minor adverse events such as bloating and diarrhea were not different between all groups.ConclusionsHigher clinical response and quality of life were demonstrated in both FMT groups than placebo. Either encapsulated FMT or FMT via rectal enema was safe and could provide favorable outcomes for IBS patients.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT06201182, Identifier: NCT06201182.